The relationships between physical fitness attributes and match demands in rugby union referees officiating the 2019 Rugby World Cup. (2nd January 2022) - Blair, Matthew R.; Scanlan, Aaron T.; Lastella, Michele; Ramsey, Codi; Elsworthy, Nathan
ABSTRACT: This study examined the relationships between physical fitness attributes and match demands in lead rugby union referees. Eleven referees underwent anthropometric and fitness assessments (40-m sprint, Yo-Yo Intermittent Recovery Test, 1.2-km shuttle run) prior to the 2019 Rugby World Cup. Match activities were assessed via global positioning system devices (total distance, high-speed running distance [>5 m·s −1 ], average speed, and peak intensities over 1-min, 5-min, and 10-min epochs) and heart rate variables were measured using chest-worn monitors (HRmean, summated-heart-rate-zones, time above 90% HRmax ). Forty-metre sprint time was significantly related to maximum speed ( P = 0.004; r = −0.79) and high-speed running distance ( P = 0.037, r = −0.63) during matches. Likewise, ∑7 skinfold thickness was significantly correlated with high-speed running distance ( P = 0.01, r = −0.72). Yo-Yo Intermittent Recovery Test, 1.2-km Shuttle Run Test, age, and body mass index exhibited non-significant correlations ( P > 0.05, r = −0.58 to 0.53) with match demand variables. Results suggest it may be pertinent for referees to optimise sprint capacity and body fat composition to execute greater high-speed running volumes and reach higher peak speeds during matches. Yo-Yo Intermittent Recovery Test and 1.2-km shuttle run tests are not correlated to specific match activity variables and thus may not be relevant for monitoring of rugby union referees.